PENGARUH KREATIVITAS DAN INOVASI TERHADAP KOMPETENSI WIRAUSAHA UMKM (STUDI KASUS PADA PELAKU USAHA DI KAMBANG IWAK, KOTA PALEMBANG): PENGARUH KREATIVITAS DAN INOVASI TERHADAP KOMPETENSI WIRAUSAHA UMKM (STUDI KASUS PADA PELAKU USAHA DI KAMBANG IWAK, KOTA PALEMBANG) - Ismail, Rizki; Saputra, Tedy Setiawan; Har, Senen (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2023)
This research aims to analyze the influence of creativity and innovation on entrepreneurial competence. The research method used was a survey using a questionnaire with a Likert scale given to 50 respondents who were MSME entrepreneurs in the city of Palembang. Entrepreneurs who operate in small businesses produce quite a lot of creative products. However, the existence of small businesses does not require growth. Many small businesses are not able to survive for long and easily experience bankruptcy. Questionnaires that have been answered by respondents are then processed and analyzed with the help of the SPSS application. The research results show that creativity does not have a positive influence on entrepreneurial competence, while innovation has a positive influence on entrepreneurial competence.